The Poole analysis in the new open economy macroeconomic framework - Mathias Hoffmann; Bernd Kempa (University of Cologne, Centre for Financial Research (CFR), 2006)
This paper evaluates simple, non-optimising monetary policy rules in the tradition of the well-known Poole analysis within a general two-country open-economy model of the New Open Economy Macroeconomic framework. Pure money supply rules are compared with simple interest rate rules for the large and the small open economy. The results for the large economy resemble those of the original Poole analysis. This is also confirmed when considering welfare. In particular, an interest rate rule yields superior results with respect to liquidity shocks whereas a money supply rule is preferable when real shock predominate. In the small open economy scenario the results of the large economy case continue to hold for domestic shocks. For foreign shocks, welfare improves under an interest rate rule relative to a money supply rule when real shocks are considered and the impact on real money balances is neglected. The reverse holds for foreign liquidity shocks. In all scenarios an interest rate rule stabilises domestic consumption.
Keywords: E32; E52; F41; 330; Monetary Policy; Poole Analysis; Exchange Rate Regimes; Welfare